1994
DOI: 10.1093/aob/74.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Photothermal Flowering Responses in Maturity Isolines of Soyabean [Glycine max (L.) Merrill] cv. Clark

Abstract: All eight isolines of three maturity genes (E(1)/e(1), E(2)/e(2), and E(3)/e(3)) of soyabean [Glycine max (L.) Merrill] cv. Clark were grown in widely different combinations of photoperiod and temperature. Under the more inductive conditions, i.e. in a warm mean temperature (30 degrees C) when daylengths were less than the critical value (i.e. less than about 13 h), the isolines flowered at similar times (23-24 d). The responses of all isolines to temperature were also similar, if not identical. Increase in da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 21 publications
4
30
0
Order By: Relevance
“…Clark NILs for the E1 , E2 , and E3 loci, Upadhyay et al (1994) found no effect of allelic substitutions at either E2 or E3 in an e1e1 background, whereas the effect of the E1 allele was marked and almost the same as that of the E2 and E3 alleles combined. Furthermore, the E2 and E3 alleles each interact positively with the E1 allele to enhance the photoperiod-sensitivity (Upadhyay et al 1994). A similar genetic interaction was observed in a combination of E4 with later-maturing genetic backgrounds (Saindon et al 1989b).…”
Section: Interaction Between Major Genes and Qtls For Floweringmentioning
confidence: 84%
See 2 more Smart Citations
“…Clark NILs for the E1 , E2 , and E3 loci, Upadhyay et al (1994) found no effect of allelic substitutions at either E2 or E3 in an e1e1 background, whereas the effect of the E1 allele was marked and almost the same as that of the E2 and E3 alleles combined. Furthermore, the E2 and E3 alleles each interact positively with the E1 allele to enhance the photoperiod-sensitivity (Upadhyay et al 1994). A similar genetic interaction was observed in a combination of E4 with later-maturing genetic backgrounds (Saindon et al 1989b).…”
Section: Interaction Between Major Genes and Qtls For Floweringmentioning
confidence: 84%
“…E1 has the largest effect on flowering (Bernard 1971, McBlain et al 1987, Upadhyay et al 1994). However, a near-isogenic line (NIL) of cv.…”
Section: Genetic Bases For Responses Of Flowering To Artificially Indmentioning
confidence: 99%
See 1 more Smart Citation
“…Soybean flowering time is regulated by both genetic and environmental factors [6, 7]. At least 11 major loci control flowering time and maturity in soybean, including E1 – E10 [817] and J [18].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, short day and high temperature accelerated the process from emergence to first flowering of soybean, whereas long day and low temperature delayed flowering time [2, 3, 7]. The interaction between photoperiod and temperature also influences soybean flowering time [2, 3, 7]. However, the genetic mechanism of photo-thermal effects on soybean flowering time is not well documented.…”
Section: Introductionmentioning
confidence: 99%